(untitled) (Fiep Bulletin - online, 2012)
This paper aims to discuss the body in the context of early childhood education. The relationship between body and education to make the reader realize that education as a product of culture, will "shaping" the behaviors and bodily habits. It draws attention to the bodily praxis performed in the context of school education, because it is tied to a conception of body that justifies and mediates. Therefore, we present briefly some theorists and their theories - especially those from psychology - as a way of exemplification that new concepts of the body has already entered the school environment and the early childhood education. Concepts that are slowly transcending the old and outdated human dualism based on the split body / mind.